Micro-Structured and Specialty Optical Fibres VI 2020
DOI: 10.1117/12.2555365
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-oxide coated LPGs for humidity sensing applications

Abstract: In this paper, we report a highly effective relative humidity (RH) sensor implemented on graphene oxide (GO) coated long period grating (LPG). The GO nanocolloides bonded onto a cylindrical fibre cladding enables the LPG with strong evanescent waves to absorb more water molecules increasing its RH sensitivity. In an LPG, the phase matching condition occurs when a forward propagating core mode is coupled with the co-propagating lower order cladding modes generating evanescent waves to interact with the surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…The sensitivity demonstrated in study is slightly higher than the study reported by Dissanayake et al (2018), where a sensitivity of 0.15 dB/%R was recorded. Additionally, the sensitivity obtained in this study was 18 times higher than the result reported by Sahoo et al (2020), which was 0.0084%/RH [69] [70]. The summaries of the three research studies that utilized long period grating as a sensing mechanism are presented in Table I.…”
Section: B) Metal Oxide Coated Long Period Grating For Humidity Sensingcontrasting
confidence: 53%
See 1 more Smart Citation
“…The sensitivity demonstrated in study is slightly higher than the study reported by Dissanayake et al (2018), where a sensitivity of 0.15 dB/%R was recorded. Additionally, the sensitivity obtained in this study was 18 times higher than the result reported by Sahoo et al (2020), which was 0.0084%/RH [69] [70]. The summaries of the three research studies that utilized long period grating as a sensing mechanism are presented in Table I.…”
Section: B) Metal Oxide Coated Long Period Grating For Humidity Sensingcontrasting
confidence: 53%
“…In 2020, research executed by Sahoo et al, also used GO as the coating material for LPG with the same deposition method [70] The graph demonstrates a noticeable reduction in the attenuation bands of the three coupled cladding modes after GO was coated on LPG. This reduction was more pronounced at for the peak observed at 1650 nm.…”
Section: B) Metal Oxide Coated Long Period Grating For Humidity Sensingmentioning
confidence: 99%
“…When water penetrates the GO, the hydrophilic group can maintain the relative interlayer distance. Therefore, as more water molecules are absorbed, the effective RI of GO decreases [31], [32]. This may change the effective RI of the propagating mode is altered, thereby affecting the wavelength shift.…”
Section: Humidity Sensing Performancementioning
confidence: 99%